Genetic Variability and Heritability in Sugarcane - Chaudhary, Rewati R (Nepal Agriculture Research Journal, 2011)
Thirty-two genotypes were evaluated in a replicated trial at Sugarcane Research Program, Jitpur, Bara, Nepal in 2000-2001 to estimate phenotypic and genotypic coefficients of variation, heritability and genetic advance for seven stalk characters in sugarcane (Saccharum officinarum L). Analysis of variance revealed highly significant differences between genotypes for all the characters studied. Genotypic variance was higher than environmental one for cane yield, millable cane number, single cane weight, stalk diameter and stalk length. A single cane weight, germination at 45 days after planting and millable cane number had high genotypic and phenotypic coefficients of variation. High heritability estimates were recorded for millable cane number, stalk diameter and single cane weight. Maximum genetic gain as percent of mean was observed for single cane weight and millable cane number. Key words: Genetic advance; Genetic variability; Heritability; Sugarcane DOI: http://dx.doi.org/10.3126/narj.v4i0.4870 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 56-59 Uploaded date: 9 June, 2011